الأداء الوظيفي للعاملين في المنظمة -دراسة نظرية - أرفيس, مريم (Changement Social, 2019)
يعتبر الأداء الوظيفي المكوّن الرئيسي للعملية الإدارية و التنظيمية للمنظمة، كونه الجزء الحي منها لأنه مرتبط بالإنسان الذي يدير العملية الإنتاجية ويحوِّل موادها الخام إلى مواد جاهزة للاستهلاك، كما أن أهمية الأداء الوظيفي لا تتوقف على مستوى المنظمة بل تتعدى ذلك إلى إنجاح خطط التنمية الاقتصادية والاجتماعية للدولة. والأداء يتكون من مجموعة عناصر منها ما هو مرتبط بمعرفة الوظيفة، ومنها ما هو مرتبط بنوعية العمل وكميته والمثابرة والوثوق والوقت المستغرق والتكلفة، وتختلف أنواعه حسب عدة معايير فحسب معيار المصدر يوجد أداء داخلي وأداء خارجي، أما حسب معيار الشمولية فيوجد أداء كلي وآخر جزئي. ومن أجل تحسين الأداء والرفع من مستواه، تقوم الإدارة بعملية التقييم من حين لآخر وفق أسس علمية وعملية مدروسة، للوصول إلى أهداف، ويوجد العديد من النظريات المفسرة للأداء الوظيفي وأشهرها النظريات الكلاسيكية للتنظيم الإداري المتأثرة Functionality is the main component of the organizational and organizational process of the organization, being the living part because it is linked to the person who manages the production process and transforms its raw materials into ready-to-consume materials, The importance of job performance does not depend on the level of the organization, but rather on the success of the economic and social development plans of the state. Performance consists of a set of elements, including what is related to knowledge of the job, including what is related to the quality of work and quantity, perseverance, reliability, time and cost, And vary according to several criteria only Source Standard There is an internal performance and external performance, and according to the standard of inclusiveness, there is total and partial performance. In order to improve the performance and raise the level, the management of the evaluation process from time to time on the basis of scientific and practical study, to reach the goals, There are many theories explaining the performance of the most famous and classical theories of administrative organization affected by the industrial revolution, Which characterized the control of the machine on the human and then the theory of human relations, which came in contradiction to it and drew attention to the human aspect of the worker. بالثورة الصناعية، والتي تميزت بسيطرة الآلة على الإنسان وبعدها نظرية العلاقات الانسانية التي جاءت مناقضة لها ووجهت الأنظار للجانب الانساني للعامل